واقع البنيات التجارية والخدماتية؛ حي النهضة نموذجا - نويرة, اسماعيل; نصيف, نادية; الخيكاني, نصير (جامعة الوادي - University of Eloued, 2021)
هدفت الدراسة إلى تشخيص واقع البنيات التجارية والخدماتية بحي النهضة، فقد إعتمادنا في دراستنا على المنهج الوصفي التحليلي، حيث أشارت الدراسة إلى أن حي النهضة يتوفر على مؤهلات واعدة من الموارد البشرية والمادية إلا أن هاته المؤهلات تعترض سبيلها بعض المعيقات كضيق المساحات التجارية، وضعف المستوى التعليمي لأغلب الباعة المتجولين، إضافة إلى تدني شروط السلامة الصحية. وعلى هذا الأساس توصلت الدراسة إلى بعض الإستنتاجات أهمها: سيادة التجارة الغير مهيكلة على النشاط التجاري والخدماتي بحي النهضة، التفاوت الحاصل على مستوى الأعمار والثفافة حيت نجد أن أغلبية التجار هم فئة غير متعلمة تعاني الأمية والجهل، عدم وجود أرضية حقيقية لتطوير البنيات التجارية والخدماتية وتعزيز مكانتها بالحي، ضعف المقاربة التشاركية وعدم الأخذ بأراء الساكنة المحلية ومراعاة خصوصياتهم المحلية عند إعداد أي مخطط للتهيئة وتنظيم المجال. : The study aimed to diagnose the reality of the commercial and service structures in the Al-Nahda district, as we relied in our study on the descriptive analytical approach, as the study indicated that the Nahda district has promising qualifications of human and material resources, but these qualifications are obstructed by some obstacles such as the narrow commercial spaces and the weak educational level For most street vendors, in addition to poor health safety conditions. On this basis, the study reached some conclusions, the most important of which are: the predominance of informal trade over commercial and service activities in the Al-Nahda district, the disparity at the level of ages and culture, where we find that the majority of merchants are an uneducated group suffering illiteracy and ignorance, the absence of a real ground for the development of commercial and service structures and strengthening their position In the neighborhood, the participatory approach was weak and the views of the local population were not taken into consideration and their local peculiarities were taken into account when preparing any plan for the preparation and organization of the field.
The reality of commercial and service structures - Al-Nahda neighborhood as a model
مقال
Keywords: البنيات ؛ ; التجارية ؛ ; الخدماتية.